Integral Rehabilitation in Dentistry - Lamas Lara, César (2012)
Nowadays is fundamental the interrelationship of the diverse specialities of dentistry for the resolution of the treatments realized in the patients who come to the odontologic consultation, since the vision slanted of some area can deprive to offer a better possibility of treatment. Working with specialists in different areas carries to orientating adequately the treatments and to optimizing results. In the present article the integral rehabilitation of a patient is detailed by the participation of the specialities of oral surgery, periodoncia, oral rehabilitation and operative dental. The obtained results were satisfactory for the patient since she recover a suitably oclusal scheme as well as the lost aesthetics. The multidisciplinary treatment in dentistry leads to optimizing the clinical results offering a more wide vision of the possibilities of treatment for the patients.